Effect of Soccer Specific Protocol on Leg Strength of University Male Soccer Players - Senthilvelan**, S. Rathinakamalan* and Dr.S. (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 1pt; margin-left: 34pt; border-left: medium none; margin-right: 34pt; padding-top: 1pt; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt; mso-border-bottom-alt: solid windowtext .5pt;"> The purpose of the study was to find out the effect of soccer specific protocol on leg strength of university male soccer players. To achieve this purpose of the study, thirty male soccer players studying in Annamalai University, Annamalai Nagar, Chidambaram, Tamil Nadu, and India were selected at random as subjects. The age of the selected subjects were from 18 to 22 years. The selected subjects were divided into two equal groups of 15 each, such as soccer specific protocol group and control group. The group-I underwent soccer specific protocol for three days per week for twelve weeks. Group-II acted as control they did not participate any special training programmes apart from their regular activities as per their curriculum. Leg strength was selected as criterion variable. The selected variable were tested by using leg lift with dynamometer at prior to and immediately after the training programme. The analysis of covariance (ANCOVA) was used to analysis the significant difference, if any between the groups. The .05 level of confidence was fixed to test the level of significance, which was considered as an appropriate. The results of the study revealed that there was significant improvement on selected criterion variable due to soccer specific protocol.